Evaluasi Kinerja pelaksanaan Anggaran Berbasis Fuzzy Inference System - Sukarna, Sukarna; Hermadi, Irman; Nurhadryani, Yani (Fakultas Ilmu Komputer, Universitas Brawijaya, 2021)
Kinerja Pemerintah merupakan output kinerja kementerian/lembaga yang diimplementasikan dalam Perjanjian Kinerja. Laporan Kinerja adalah bentuk pertanggungjawaban kementerian terhadap Perjanjian Kinerja yang disusun secara bertahap dari unit kerja, unit organisasi, dan kementerian. Capaian kinerja aggaran tingkat Kementerian Pertanian tahun 2019 sebesar 94.56% (kategori sangat baik) namun nilai efisiensi anggaran tingkat kementerian sebesar 71,89% yang disebabkan oleh belum efisiennya penggunaan anggaran terhadap capain target. Penelitian ini menggunakan fuzzy inference system Mamdani untuk menentukan status capaian kinerja di unit kerja Balai Pengkajian Teknologi Pertanian (BPTP) Jawa Tengah berdasarkan Peraturan Menteri Keuangan nomor 214 tahun 2017. Aspek penilaian terdiri dari aspek manfaat dan aspek implementasi. Hasil penelitian ini adalah monitoring dan evaluasi kinerja tingkat unit kerja berupa status capaian kinerja berdasarkan realisasi anggaran riil dengan kriteria sangat kurang, kurang, cukup, baik, dan baik sekali. Implementasi sistem berbasis web dengan nilai evaluasi usability menggunakan use questionnaire untuk masing-masing kategori yaitu US sebesar 5.98, EU sebesar 5.25, EL sebesar 5.75, dan SC sebesar 5.17. Pengujian status capaian kinerja unit kerja than 2019 dengan penilaian pakar menujukkan hasil yang sama yaitu kategori sangat baik. AbtractGovernment performance was the output of the performance of the ministry/agency implemented in the performance agreement. Performance report was a form of ministerial accountability to performance agreements that were arranged in stages from work units, organizational units, and ministries. The achievement of the budget performance at the ministry of agriculture in 2019 was 94.56% (very good category) but the efficiency value of the ministry leveled budget was 71.89% due to the inefficient used of the budget towards target achievement, it is necessary to monitoring and evaluate budget performace. Measurement and assesment of the achievement of budget execution performance based on PMK Number 214 of 2017 consists of implementation aspects (budget absorption, consistency between planning and implementation, achievement of outputs, and efficiency). The studied objective was to facilitate works units in monitoring and evaluate budget performance by presenting accurate and actual performance information as a function of internal control using the mamdani fuzzy inference system to determine the status of performance achievements. Mamdan’s model can describe skills for intuitive problems that have an output in the form of values in the domain of fuzzy sets categorized under the linguistic component. The results of this studied are monitoring and evaluation of the web-based work unit in the form of real performance status as a basis for preparing recommendations in order to improve budget performance. The usability evaluation of the system used a use questionnaire for each category, namely US 5.98, EU 5.25, EL 5.75, and SC 5.17. Whitebox testing against 25 rule bases shows the results as expected. Testing the status of work unit performance achievements in 2019 with expert assessments shows the same results, namely the very good category.